Metformin with Versus without Concomitant Probiotic Therapy in Newly Diagnosed Patients with Type 2 Diabetes or Prediabetes: A Comparative Analysis in Relation to Glycemic Control, Gastrointestinal Side Effects, and Treatment Compliance - Şahin, Kübra; Şahintürk, Yasin; Köker, Gökhan; Özçelik Köker, Gülhan; Bostan, Feyzi; Kök, Mehmet; Uyar, Seyit; Çekin, Ayhan Hilmi (Turkish Journal of Gastroenterology, 2022)
Background: To evaluate the impact of concomitant use of probiotic BB-12 in metformin-treated patients with type 2 diabetes or prediabetes on glycemic control, metformin-related gastrointestinal side effects, and treatment compliance. Methods: A total of 156 patients (mean [standard deviation] age: 50.9 [9.9 years], 74.4% females) with newly diagnosed type 2 diabetes or prediabetes were randomly assigned to receive either metformin alone (n = 84, MET group) or metformin plus Bifidobacterium animalis subsp. lactis (BB-12) probiotic (n = 72, MET-PRO group). Data on body mass index (kg/m2), fasting blood glucose (mg/dL), blood lipids, and glycated hemoglobin (HbA1c) levels were recorded at baseline and at the third month of therapy. Data on gastrointestinal intolerance symptoms and treatment noncompliance were also recorded during post-treatment week 1 to week 4. Results: MET-PRO versus MET therapy was associated with a significantly higher rate of treatment compliance (91.7% vs 71.4%, P = .001), greater reduction from baseline HbA1c values (0.9 [0.4-1.6] vs 0.4 [0-1.6] %, P < .001) and lower likelihood of gastrointestinal intolerance symptoms, including abdominal pain (P = .031 to <.001), diarrhea (P = .005 to <.001) and bloating (P = .010 to <.001). Noncompliance developed later (at least 15 days after the therapy) in a significantly higher percentage of patients in the MET group (P = .001 for 15–21 days and P = .002 for 22–28 days). Conclusion: In conclusion, the present study proposes the benefit of combining probiotics with metformin in the treatment of patients with T2D or prediabetes in terms of improved glycemic control and treatment adherence rather than correction of dyslipidemia or weight reduction. Cite this article as: Şahin K, Şahintürk Y, Köker G, et al. Metformin with versus without concomitant probiotic therapy in newly diagnosed patients with type 2 diabetes or prediabetes: A comparative analysis in relation to glycemic control, gastrointestinal side effects, and treatment compliance. Turk J Gastroenterol. 2022;33(11):925-933.